Factors That Affect Crossover Between Multiple Worlds Within a Narrative. Issue 8 (17th November 2018) - Chan, Greta C.; Foy, Jeffrey E.; Magliano, Joseph P.
ABSTRACT: In some narratives one world is embedded within the main world of the story, which we refer to as the base world, and elements from one world can cross over into the other. This study explored the conditions in which readers perceive character crossover as being likely to occur. Participants read stories that set up the potential for a character from an embedded world to cross over into the base world. Across four experiments we varied the similarity between the embedded world and the base world and the genre of the story worlds. Participants believed crossover would be more likely (Experiments 1–3), and it was processed more easily (Experiment 4), as measured by reading times, when the base world was fantastic than when it was realistic. The similarity between story worlds mattered when the base world was realistic, with character crossover being more probable and processed more easily when overlap was high. These results have implications for recent research on the barriers between narrative worlds.